Negative erosion and negative emissions: Combining multiple land-based carbon dioxide removal techniques to rebuild fertile topsoils and enhance food production - Janssens, Ivan A.; Roobroeck, Dries; Sardans, Jordi; Obersteiner, Michael; Peñuelas, Josep; Richter, Andreas; Smith, Pete; Verbruggen, Erik; Vicca, Sara (Frontiers in Climate, 2022)
Carbon dioxide removal (CDR) that increases the area of forest cover or bio-energy crops inherently competes for land with crop and livestock systems, compromising food security, or will encroach natural lands, compromising biodiversity. Mass deployment of these terrestrial CDR technologies to reverse climate change therefore cannot be achieved without a substantial intensification of agricultural output, i.e., producing more food on less land. This poses a major challenge, particularly in regions where arable land is little available or severely degraded and where agriculture is crucial to sustain people’s livelihoods, such as the Global South. Enhanced silicate weathering, biochar amendment, and soil carbon sequestration are CDR techniques that avoid this competition for land and may even bring about multiple co-benefits for food production. This paper elaborates on the idea to take these latter CDR technologies a step further and use them not only to drawdown CO2 from the atmosphere, but also to rebuild fertile soils (negative erosion) in areas that suffer from pervasive land degradation and have enough water available for agriculture. This way of engineering topsoil could contribute to the fight against under- and malnutrition in areas where crop and livestock production currently is hampered by surface erosion and nutrient depletion, and thereby alleviate pressure on intact ecosystems.